ELIT POLITIK LOKAL DALAM KONFLIK IBUKOTA DI KABUPATEN MOROWALI - DARWIS, DARWIS (Universitas Muhammadiyah Yogyakarta, 2011)
Conflict in the district capital of Morowali placement lasted about five years since its establishment asthe new regional autonomy in Indonesia based on Law No. 51/1999. This regulation provides that theCentral region was the capital of the definitive Bungku Morowali district. Kolonodale areas that aredesignated as temporary capital of less than five years Over the functioning of the capital while inKolonodale, more accelerated development in the region, while the Middle Bungku not accelerating development.This is a factor of conflict. In fact, the split at the level of local political elites in both localgovernment agencies as well as implications for the local parliament Morowali community in twogroups of different ethnic communities of religious, ethnic Bungku the Muslim majority and ethnicMori generally Christian. Conflicts of capital and then rolled into the realm of the existence of a secondbout of ethnic communities is the result of mass mobilization which is anarchy. Conflict with thediscourse in society is important for the transfer of capital into the local political elite to exploit themomentum of mass localization facing the 2004 election and the Election of Regent Morowali (localelection) 2007